Desempenho, acesso e litigiosidade: discussões metodológicas acerca da quantificação do acesso à justiça - Sátiro, Renato Máximo (2022)
It is observed that organizational performance is one of the most important concepts for research in Administration; the Public Power is not immune to this finding. In spite of the importance of studying the elements relating to the Powers of the State and – notably – of the Judiciary, it is observed that there are few studies that deal with the aforementioned Power, even more scarce the studies that deal with the object in a quantitative way. One of these fields of research deals with access to justice, perhaps the most basic element of a so-called democratic regime and which, invariably, permeates the realization of all other rights provided for in a given legal order, but which, in the same way, has not received due attention from science. Based on the above, the objective of the present study is to analyze the performance of justice organizations in Brazil from the perspective of access to justice. The results indicate that the issue of judicial access is a multidisciplinary and complex factor, for which several issues compete. Issues related to the very structure of the Judiciary; issues related to the inadequacy of the legal framework edited under the aegis of an individualistic social conception of conflict; issues still linked to the lack of effectiveness of the Executive and Legislative powers, which transfer certain responsibilities to the Judiciary, among several other factors.